Post-harvest of onion due to fertilization with micronutrient (Research, Society and Development, 2022)
The onion (Allium cepa L.) is the third most cultivated vegetable and has great socioeconomic importance worldwide. Because it is highly perishable and has greater demand than supply, many post-harvest losses occur, most of them caused by inadequate storage conditions affecting the bulbs quality. This study aimed to evaluate the postharvest quality of onion as a function of fertilization with micronutrients, using the cultivar “Rio das antas”. The experiment was divided into two stages: field and laboratory. In the field, an experiment was installed between June and December 2019 at Experimental Farm Rafael Fernandes, in completely randomized blocks with nine treatments and four replications. The treatments consisted of the combined doses of B, Cu and Zn. In the laboratory, the experimental design was in completely randomized blocks in 9 x 4 split-plot design, with four replications. The treatments (micronutrients B, Cu and Zn) were arranged in the plots and the storage times were arranged in the subplots (0; 20; 40 and 60 days after harvest). Bulb firmness, soluble solids (ºBrix), total soluble sugars and pungency were evaluated. The data were subjected to statistical analysis as a function of storage time, by the Sisvar program, applying regression analysis. The combined application of doses of 1-4-1 kg.ha-1 of Boron, Copper and Zinc, respectively, presented the best results for pungency, firmness and sugars during storage, this being the most recommended treatment for not significantly different from higher doses, promoting more efficient use of inputs.